TEACHER OF HIGHER SCHOOL: WHAT WILL IT BE?(Reflections on social expectations and professional realities) - Lyudmila F. Krasinskaya (Высшее образование в России)
The article reveals the contradiction between the social expectations of higher school teachers and the real environment of their professional activities. On the one hand, there are new requirements for the competence of teachers, due to the tendencies of education development, and above all the rapid development of information technology. On the other hand, teachers are in the unfortunate situation caused by costs of the state educational policy (bureaucratization of universities, reduction of the staff, worsening of working conditions, increasing the load and others), as well as ineffective internal control, imbalance of interests of the administration and employees.